User Perceptions Toward Gamification in Digital Sharia Savings: Persepsi Pengguna Terhadap Gamifikasi dalam Tabungan Syariah Digital - Muhammad Andreansyah Ilham Sembiring Andre; Sri Ramadhani; Muhammad Syahbudi (Academia Open, 2025)
General Background: The rapid digital transformation in Indonesia's Islamic banking sector aims to improve service quality and financial inclusion through mobile applications. Specific Background: Despite technological advancements, user engagement with digital Islamic savings remains low, highlighting a need for innovative strategies. Knowledge Gap: Limited research exists on the role of gamification in enhancing engagement with Sharia-based digital financial products, especially outside Java. Aims: This study investigates user perceptions of gamification elements—such as daily missions, challenges, and progress bars—on engagement with Bank Jago Syariah's mobile savings platform in Medan. Results: Using the Technology Acceptance Model, findings from 30 users show that perceived enjoyment (score: 85), usefulness (82), and intention to use (81) are all rated highly. Qualitative insights confirm that gamification motivates users and improves satisfaction. Novelty: This research offers a regional perspective from Medan, filling a geographic and thematic gap by integrating Sharia values with gamification design. Implications: The results suggest that interactive, Sharia-compliant gamification features can effectively boost user loyalty and should be strategically implemented in Islamic fintech development.Highlight : Gamification such as daily missions and progress bars were shown to increase user motivation and engagement. Perceived Enjoyment scored the highest, indicating fun to be a key factor in feature adoption. Customization of features with Shariah values and user-friendly interfaces are recommended to increase loyalty. Keywords : Gamification, Tabungan Syariah Digital, Keterlibatan Pengguna, TAM, Bank Jago Syariah